2020
DOI: 10.1002/ptr.6820
|View full text |Cite
|
Sign up to set email alerts
|

The effect of concentrated pomegranate juice consumption on risk factors of cardiovascular diseases in women with polycystic ovary syndrome: A randomized controlled trial

Abstract: Polycystic ovary syndrome (PCOS) is associated with insulin resistance and dyslipidemia. Pomegranate juice is a rich source of polyphenols that may improve blood pressure, lipid profile, and other risk factors of cardiovascular diseases (CVDs). No study has examined the effects of pomegranate juice consumption on the clinical outcomes of PCOS. This study aimed to examine the effects of concentrated pomegranate juice (CPJ) consumption on risk factors of CVDs in women with PCOS. In this randomized clinical trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 47 publications
0
36
0
Order By: Relevance
“…Nevertheless, another study found a pomegranate extract reduction effect on DBP without any effect on SBP (Stockton et al, 2017). Three clinical trials with different subjects (polycystic ovary syndrome, healthy individuals, and hypertension) that used pomegranate juice or its concentrate showed a significant reduction in SBP and DBP (Abedini, Ghasemi‐Tehrani, Tarrahi, & Amani, 2021; Asgary et al, 2014; Tsang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, another study found a pomegranate extract reduction effect on DBP without any effect on SBP (Stockton et al, 2017). Three clinical trials with different subjects (polycystic ovary syndrome, healthy individuals, and hypertension) that used pomegranate juice or its concentrate showed a significant reduction in SBP and DBP (Abedini, Ghasemi‐Tehrani, Tarrahi, & Amani, 2021; Asgary et al, 2014; Tsang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Ovosicare® Fertility also contains pomegranate extract (Pomanox®) which is a well-known antioxidant. It has been described that polyphenols present in the pomegranate extract have scavenger activity that can have a beneficial effect in preventing ovarian oxidative stress [54,55]. Importantly, numerous reports have shown a relationship between increased ROS and inflammatory factors such as IL1-β, which are intimately linked to ovarian aging [56,57].…”
Section: Discussionmentioning
confidence: 99%
“…Two systematic reviews published after guideline inception support altered carbohydrate intake to improve intermediate markers of PCOS [55,56], finding that altering carbohydrate type, as opposed to content, is preferable to better manage PCOS [55]. RCTs [57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72] and pre-post intervention studies [73][74][75][76][77][78][79][80] demonstrate that following a low GI/GL diet for at least eight weeks significantly reduces WC [55,73,74] and BMI when compared to high GI/GL [56] or a regular diet [73][74][75][76], although levels of weight loss are generally comparable to other dietary compositions [59,60,72,74]. These reductions are proposed to be a result of decreased hunger, which may reduce energy intake and make it easier to follow dietary recommendations in the long-term [78,[81][82][83][84].…”
Section: Carbohydratesmentioning
confidence: 99%
“…Studies examining specific food items in relation to PCOS outcomes, including raw onions [65], concentrated pomegranate juice [69,[113][114][115] and flaxseed powder [70,116] have yielded largely inconsistent results. A core limitation of these single food studies is that foods are never consumed alone within the diet, omitting the influence of the dietary matrix and the interactions that occur amongst dietary constituents within meals.…”
Section: Dietary and Eating Patternsmentioning
confidence: 99%